Higher education students’ perceptions of the CBSUA’s IDIG-funded free Wi-Fi project: Access, usage, well-being, and challenges - Dacer, Christopher B. (Edelweiss Applied Science and Technology, 2025)
The availability of free Wi-Fi provided by the Commission on Higher Education (CHED) Institutional Development and Innovation Grant (IDIG), in partnership with the Central Bicol State University of Agriculture (CBSUA), across its four campuses aims to enhance students’ learning experiences by providing access to educational resources, communication tools, and online platforms for flexible learning. A total of 103 student beneficiaries participated in the study, selected through a purposive random sampling method. Using a convergent parallel mixed-method design, both survey questionnaires and interviews were employed to capture students’ experiences. Findings revealed that while the free Wi-Fi program provided equitable access to online resources and supported asynchronous learning, significant barriers limited its effectiveness. Students reported slow internet speed, dropped connections, usage restrictions, and limited coverage as common problems. These challenges hindered their ability to participate actively in online classes and reduced opportunities for social connectedness. Despite these issues, students acknowledged that the project helped them download course materials, complete asynchronous tasks, and reduce the stress of securing mobile data. The study suggests that institutional Wi-Fi initiatives can help bridge aspects of the digital divide, but they require stronger infrastructure, policy adjustments, and effective student support systems to maximize their benefits. These findings are significant for enhancing CBSUA’s educational programs and services by ensuring inclusive access to digital learning.